POLA PENGGUNAAN TANAMAN OBAT TRADISIONAL DI DESA SEGARA KEMBANG DAN DESA TUNGKU JAYA DI KABUPATEN OGAN KOMERING ULU - Sitorus, Hotnida; Salim, Milana; Ambarita, Lasbudi Pertama (Publikasi Penelitian Terapan dan Kebijakan, 2011)
Traditional ethnic groups in Indonesia have a characteristic and distinct cultural identity, so most likely the perception and conception of society toward plant-based resources in their environment is also different, including the use of plants as traditional medicine. This research triesto explore the types of local medicinal plants used to treat specific diseases and usage behavior of traditional medicinal plants in Ogan Komering Ulu. This research is a non-intervention with cross sectional design conducted in Desa Segara Kembang and Desa Tungku Jaya. Data collectionthrough interviews using a structured questionnaire and observation of medicinal plants. Description of the behavior of the use of traditional medicine in general, people use traditional medicine as a companion to other drugs to treat disease (Desa Segara Kembang = 63%, DesaTungku Jaya = 84,3%). This type of traditional medicine often use derived from plants (Desa Segara Kembang = 98,8%, Desa Tungku Jaya = 80,9%). Most of the reason for its use due to the ancestral traditions from generation to generation (Desa Segara Kembang = 61,9%, Desa TungkuJaya = 47,2%). Traditional medicinal plants are usually obtained from its own garden (Desa Segara Kembang = 44%, Desa Tungku Jaya = 58,3%). The use of traditional medicines majority used in the treatment of diseases (Desa Segara Kembang = 72,6%, Desa Tungku Jaya = 91,7%). Parts ofthe plant often used are tubers, roots, leaves, fruits, stems, flowers and bark.